Reference pricing in the presence of pseudo-generics - Gonçalves, Ricardo (2016)
We build on the analysis of Rodrigues et al. (2011) and look at the market impact of pseudo- generics under two possible reimbursement mechanisms: reference pricing and xed percentage reimbursement. Reference pricing emerges as a preferable reimbursement mechanism, both from a consumer s perspective as well as from a welfare perspective, particularly when a pseudo- generic is present. JEL Classi cation: I18, L13